(untitled) (Research, Society and Development, 2023)
COVID-19 is a disease caused by the SARS-CoV-2 virus with mild to severe manifestations, as well as leading to death. Studies have shown that patients hospitalized for the disease have persistent symptoms even after a long period of discharge, with an impact on quality of life. Objective: To evaluate the sociodemographic characteristics, persistent symptoms and quality of life of patients after hospitalization due to COVID-19 in a municipality in the southwest of Paraná. Methodology: This is a descriptive-exploratory, field, cross-sectional study with a quantitative approach, performed with patients who were hospitalized due to COVID-19, after hospital discharge in a municipality in the southwest of Paraná. A sample calculation was performed, so the research consisted of fifty (50) patients. A semi-structured questionnaire was used to assess demographic variables and clinical data of hospitalization, in addition to the WHOQOL-BREF instrument; the Medical Research Council dyspnea scale and the Visual Analogue Pain Scale. Results: It was observed that 66% of the evaluated patients were male, the majority being young, with complete primary education, married, with chronic diseases, with emphasis on arterial hypertension and obesity. It was found that most of them have persistent symptoms, predominantly impaired memory and arthralgia, even after a long period of hospital discharge, generating a negative impact on quality of life. Conclusion: Patients who were hospitalized for COVID-19, especially young men, with comorbidities, have persistent symptoms after a long period of hospital discharge, with a negative impact on quality of life, highlighting the need for long- term follow-up for such patients.